\(\hept{\begin{cases}x^2+2xy+2y^2=2y+1\\3x^2+2xy-y^2=2x-y+5\end{cases}}\)
\(\Rightarrow4x^2+4xy+y^2=2x+y+6\)
\(\Rightarrow\left(2x+y\right)^2-\left(2x+y\right)=6\)
\(\Rightarrow\left(2x+y\right)\left(2x+y-1\right)=6\)
.........
\(\hept{\begin{cases}x^2+2xy+2y^2=2y+1\\3x^2+2xy-y^2=2x-y+5\end{cases}}\)
\(\Rightarrow4x^2+4xy+y^2=2x+y+6\)
\(\Rightarrow\left(2x+y\right)^2-\left(2x+y\right)=6\)
\(\Rightarrow\left(2x+y\right)\left(2x+y-1\right)=6\)
.........
giải các hệ phương trình sau
a) \(\hept{\begin{cases}x^2+y^2-2xy=1\\2x^2+2y^2-2xy-y=0\end{cases}}\)
b)\(\hept{\begin{cases}xy+2x-y-2=0\\xy-3x+2y=0\end{cases}}\)
giải hệ phương trình bằng phương pháp thế
\(â,\hept{\begin{cases}3x^2+\left(6-y\right)x^2-2xy=0\\x^2-x+y=-3\end{cases}}\)
\(b,\hept{\begin{cases}x^2+y^2+xy+1=4y\\y\left(x+y\right)^2=2x^2+7y+2\end{cases}}\)
\(c,\hept{\begin{cases}x^4+2x^3y+x^2y^2=2x+9\\x^2+2xy=6x+6\end{cases}}\)
\(d,\hept{\begin{cases}x\sqrt{y+1}=1\\x^2y=y-1\end{cases}}\)
giải hệ phương trình
1)\(\hept{\begin{cases}x^2+xy+y^2=3\\x^3+2y^3=y+2x\end{cases}}\)
2) \(\hept{\begin{cases}\frac{y^2+1}{y}=\frac{x^2+1}{x}\\x^2+3y^2=4\end{cases}}\)
3)\(\hept{\begin{cases}x^2+y^4-2xy^3=0\\x^2+2y^2-2xy=1\end{cases}}\)
Giải hệ phương trình
\(\hept{\begin{cases}2x^2+3xy+2x+y=0\\x^2+2xy+2y^2+3x=0\end{cases}}\)
cho hệ phương trình \(\hept{\begin{cases}5x^2+2y^2+2xy=26\\3x+\left(2x+y\right)\left(x-y\right)=11\end{cases}}\)
Giải hệ phương trình:
\(1,\hept{\begin{cases}x^2+5x+y=9\\3x^3+x^2y+2xy+6x^2=18\end{cases}}\)
\(2,\hept{\begin{cases}x^3+7y=\left(x+y\right)^2+x^2y+7x+4\\3x^2+y^2+8y+4=8x\end{cases}}\)
Giải hệ phương trình \(\hept{\begin{cases}x^2-2xy+x-2y+3=0\\y^2-x^2+2xy+2x-2=0\end{cases}}\)
Giải hệ phương trình: \(\hept{\begin{cases}x^2-2xy+x-2y+3=0\\y^2-x^2+2xy+2x-2=0\end{cases}}\)
Giải hệ phương trình:\(\hept{\begin{cases}x^2+y^2=4z-5+2xy\\x^4+y^4=9z-5-2x^2y^2-4z^2\end{cases}}\)